Morphology and Stomach Content Analysis of Green Rough-backed Puffer Fish, Lagocephalus lunaris from Kuching, Sarawak - Mohamad, Samsur; Isa, Fadhilah Isa (Borneo Journal of Resource Science and Technology, 2016)
A total of 101 individuals of green rough-backed pufferfish, Lagocephalus lunaris were collected at two sampling sites and were assessed for their morphological characteristics and diet by stomach content analysis. The physical characteristics were observed and body weight (BW), total length (TL), standard length (SL) and number of fin rays were recorded. The results showed that the physical body measurement in all individuals were almost similar in their range of size (TL: 8.6 ± 0.3 cm; SL: 7.0 ± 0.2 cm; BW: 14.3 ± 1.5 g) and most individual had same distribution of spines at the dorsal part which extended to dorsal fin. The numbers of caudal, dorsal, pectoral and anal fin rays ranged from 5 to 12, 7 to 11, 9 to 12 and 7 to 17, respectively. Analysis of the diet composition showed that fish is carnivorous which prey on crabs, prawns, small fish and squids. Based on index of relative importance, crabs were identified as most important prey in Site 1 and Site 2, with value of (47.5, 55.6%), and followed by prawns (36.3, 38.2%), fish (5.6, 11.2%), squids (0.7, 2.9%) and bivalves (0.1, 1.7%). Our results suggest that L. lunaris had unique spines distribution shape which important for species identification and it consumed mainly on crustacean as diet composition. To our knowledge, this is the first attempt to describe morphological characteristics and stomach content of L. lunaris which inhabit in Sarawak waters.